T64. LINKING SUBCLINICAL PERSECUTORY IDEATION TO INFLEXIBLE SOCIAL INFERENCE UNDER UNCERTAINTY. (18th May 2020) - Wellstein, Katharina; Diaconescu, Andreea; Mathys, Christoph; Bischof, Martin; Rüesch, Annia; Paolini, Gina; Aponte, Eduardo A; Kasper, Lars; Ullrich, Johannes; Enno Stephan, Klaas
Abstract: Background: Persecutory delusions (PD) are a prominent symptom in first episode psychosis and psychosis patients. PD have been linked to abnormalities in probabilistic reasoning and social inference (e.g., attribution styles). Predictive Coding theories of delusion formation suggest that rigid delusional beliefs could be formalized as precise (i.e. held with certainty) high-level prior beliefs, which were formed to explain away overly precise low-level prediction errors (PEs). Rigid reliance on high-level prior beliefs would in turn lead to diminished updating of high-level PEs, i.e. decreased learning and updating of high-level beliefs. Methods: We tested the prediction that subclinical PD ideation is related to altered social inference and beliefs about others' intentions. To that end, N=1'145 participants from the general population were pre-screened with the Paranoia Checklist (PCL) and assigned to groups of high ("high PD") or low PD tendencies ("low PD"). Participants with intermediate scores were excluded, participants assigned to either group filled in the PCL again after four weeks, only individuals whose score remained inside the cut-offs for either group were subsequently invited to the study. We invited 162 participants and included 151 participants in the analyses based on exclusion criteria defined in an analysis plan, which was time-stamped before the conclusion of data acquisition. Participants performed a probabilistic advice-taking task with dynamic changes in the advice-outcome mapping (volatility) under one of two experimental frames. These frames differentially emphasised possible reasons behind unhelpful advice: (i) the adviser's possible intentions (dispositional frame) or (ii) the rules of the game (situational frame). Our design was thus 2-by-2 factorial (high vs. low delusional ideation, dispositional vs. situational frame). Participants were matched regarding age, gender, and education in years. In addition to analyses of variance on participants' behaviour, we applied computational modeling to test the predictions regarding prior beliefs and belief updating mentioned above. Results: We found significant group-by-frame interactions, indicating that in the situational frame high PD participants took advice less into account than low scorers (df = (1, 150), F = 5.77, p = 0.018, partial η2= 0.04). This was also reflected in the model parameters of the model explaining participants' learning under uncertainty best in comparison to other learning models (e.g. tonic evolution rate omega2: df = (1, 150), F = 4.75, p = 0.03). Discussion: Our findings suggest that social inference in individuals with subclinical PD tendencies is shaped by rigid negative prior beliefs about the intentions of others. High PD participants were less sensitive to the attributional framing and updated their beliefs less vs. low PD participants thereby preventing them to make adaptive use of social information in "safe" contexts.